Streptococcus pneumoniae Coinfection in COVID-19: A Series of Three Cases - Chaitanya Pal; Paulina Przydzial; Ogechukwu Chika-Nwosuh; Shrey Shah; Pratik Patel; Nikhil Madan (Case Reports in Pulmonology)
Bacterial coinfections are not uncommon with respiratory viral pathogens. These coinfections can add to significant mortality and morbidity. We are currently dealing with the SARS-CoV-2 pandemic, which has affected over 15 million people globally with over half a million deaths. Previous respiratory viral pandemics have taught us that bacterial coinfections can lead to higher mortality and morbidity. However, there is limited literature on the current SARS-CoV-2 pandemic and associated coinfections, which reported infection rates varying between 1% and 8% based on various cross-sectional studies. In one meta-analysis of coinfections in COVID-19, rates of Streptococcus pneumoniae coinfections have been negligible when compared to previous influenza pandemics. Current literature does not favor the use of empiric, broad-spectrum antibiotics in confirmed SARS-CoV-2 infections. We present three cases of confirmed SARS-CoV-2 infections complicated by Streptococcus pneumoniae coinfection. These cases demonstrate the importance of concomitant testing for common pathogens despite the need for antimicrobial stewardship.